Analisis Pengaruh Inflansi, Tingkat Pengangguran Terbuka Dan Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi Diprovinsi Lampung (2013-2022) - Serli Agustia; Siti Chotifah Hastuty; Viska Rahmawati; Muhammad Kurniawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to analyze the influence of inflation, open unemployment rates, and poverty rates on economic growth in Lampung Province during the 2013-2022 period. Secondary data related to inflation, open unemployment rate, poverty rate and economic growth in Lampung Province were collected from the Central Statistics Agency (BPS). The analysis was carried out using the multiple linear regression method. The research results show that inflation has a significant positive influence on economic growth, while the open unemployment rate and poverty rate do not have a statistically significant influence. These findings contribute to understanding regional economic dynamics and can be the basis for formulating more effective policies to support sustainable economic growth in Lampung Province.